Harnessing the Power of Gamification: A Deep Learning Approach to Enhancing Vocabulary Retention in EFL Classroom - Abdul Gafur Marzuki; Huriyah; Anita; Risa Triassanti; Dewi Kencanawati; Santiana (Jurnal Edutech Undiksha, 2025)
Vocabulary is essential in EFL learning, yet retention, motivation, and engagement remain challenges. This study aims to explore the effectiveness of deep learning–based gamification in improving these aspects through more interactive and adaptive learning. The research subjects consisted of 30 students and 10 English teachers selected through purposive sampling based on their experience with gamification-based learning. Data were collected through semi-structured interviews, classroom observations, and document analysis using interview guidelines, observation checklists, and learning material reviews as research instruments. The data were analyzed using thematic analysis supported by triangulation and member checking techniques to ensure the validity of the findings. The results indicate that the implementation of gamification enhances vocabulary retention and promotes students’ motivation and engagement through interactive features such as progressive challenges, point systems, and immediate feedback. This study concludes that the integration of gamification with deep learning–based educational technology is a promising strategy for improving the effectiveness of EFL vocabulary learning and provides implications for the development of technology-enhanced language teaching practices.